Tanda Masuk Waktu Salat dalam Perspektif Hukum Islam dan Ilmu Falak - Ismail, Ismail; T. Yasin, Dikson; Ukhti, Laiyina (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2023)
Signs for entering prayer times are still hotly discussed in Indonesia, especially the sign for entering the time for the Fajr prayer. This paper tries to describe the signs of prayer times from the point of view of Islamic law and astronomy. With a normative descriptive approach, it is hoped that this paper can find answers to the problem of entering prayer times in Indonesia. Signs of entering pure prayer times are based on the apparent circulation of the sun. There are three kinds of daily phenomena of the sun which are used as a sign of entering the prayer time. The shadow of the sun for the sign of entering the time for the Zuhur and Asar prayers. The sun disk is a sign of entering the time for the Maghrib prayer. The bias of sunlight for the sign of entering the time of Isha and Fajr prayers. The sun sign is changed in the form of the height of the sun which is adjusted to the daily time angle of the sun, so that each entry in the sign can be easily translated in the standard form of time in the respective area.